Metáforas cognitivas propias del discurso de la prensa de mujeres: el ejemplo de CUIDAR EL CUERPO ES UNA BATALLA - Lamża, Zuzanna (Neophilologica, 2012)
The aim of this article is to show how the abstract concept of care for the body is conceptualized by cognitive metaphors. I decided that the most interesting and promising study material will be women’s magazines: in my analysis I shall use metaphorical expressions describing bodycare coming from three magazines (each in three language versions: Polish, English and Spanish) with differing amounts of ‘informative’ content concentrated on fashion and body, yet all almost devoid of non-persuasive journalism. The more aware and resilient against direct advertising is the consumer, the stronger is the need of publishers to hide the message in quasi-articles or between the lines of a quasi-interview. It’s then no surprise that the skillful use of M. Johnson’s and G. Lakoff’s theory of the conceptual metaphor — providing the advertisers with a powerful and versatile tool than practically cannot be abused (because it has infinite possible individual realizations in the text and is at the same time transparent for the reader) — became one of the key issues in marketing.